2010
DOI: 10.5336/medsci.2009-12604
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Data for Management of Lateral Epicondylitis: Review

Abstract: Ö ÖZ ZE ET T Bu der le me de la te ral epi kon di lit (LE) te da vi sin de de nen miş çok çe şit li te da vi yön tem le ri nin ka nı ta da ya lı ve ri le ri nin su nul ma sı amaç lan mış tır. Op ti mal te da vi se çi mi için ka nı ta da ya lı bi limsel ve ri ler kul la nıl ma lı dır. Ay rı ca güç lü ve za yıf ka nıt lar ile ri kli nik araş tır ma la rın plan lan ma sı açı sın dan önem li dir. Coc hra ne Kü tüp ha ne si, dü zen li ola rak gün cel leş ti ri len, ka nı ta da ya lı tıp ve rita ban la rı ko lek si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Stratford et al evaluated the effectiveness of US alone or in combination with friction massage for decreasing pain in LE and indicated similar results for each group [9,27]. Studies with US, alone or combined with other modalities, concluded more functional and pain improvement than in placebo groups [5,8,9,14]. Also a systematic review showed beneficial effects of US alone or in combination with other treatments with regard to decreasing pain in the treatment of patients with LE [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Stratford et al evaluated the effectiveness of US alone or in combination with friction massage for decreasing pain in LE and indicated similar results for each group [9,27]. Studies with US, alone or combined with other modalities, concluded more functional and pain improvement than in placebo groups [5,8,9,14]. Also a systematic review showed beneficial effects of US alone or in combination with other treatments with regard to decreasing pain in the treatment of patients with LE [9].…”
Section: Discussionmentioning
confidence: 95%
“…ESWT group 8 (0-14) 9 (2-14) 9 (2-14) 9 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) BT before treatment, AT after treatment Table 5 The changes in the VAS pain scores of the patients at first, third, and sixth months according to the treatment groups BT before treatment, AT after treatment Table 7 The changes in pinch strength scores of the patients at first, third, and sixth months according to the treatment groups BT before treatment, AT after treatment Table 6 The changes in the grip strength scores of the patients at first, third, and sixth months according to the treatment groups BT before treatment, AT after treatment the use of ESWT due to the lack of convincing evidence in regard to its effectiveness [20,21]. In our study, ESWT treatment was applied every other day without any local anesthesia for ten sessions and any side effect was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In LE treatment, it is crucial to avoid repeated wrist movements, heavy lifting, and activities that increase the pain. [ 16 ] Therefore, wrist splints and elbow orthoses are frequently used. Altan and Kanat[ 17 ] reported that, in LE treatment, both lateral epicondyle straps and wrist splints reduce pain, and there was no difference between the two splints for long-term efficacy.…”
Section: Discussionmentioning
confidence: 99%